MiR-30a: A Novel Biomarker and Potential Therapeutic Target for Cancer. (6th August 2018) - Jiang, Lin-hong; Zhang, He-da; Tang, Jin-hai
Abstract : MicroRNAs (miRNAs) are small, highly conserved noncoding RNAs molecules, consisting of 18–25 nucleotides that regulate gene expression by binding to complementary binding sites within the 3′untranslated region (3′UTR) of target mRNAs. MiRNAs have been involved in regulating gene expression and diverse physiological and pathological processes. Several studies have reported that miR-30a, situated on chromosome 6q.13, is produced by an intronic transcriptional unit. Moreover, miR-30a has demonstrated its role in biological processes, including inhibiting proliferation and metastasis in many tumors, autophagy in chronic myelogenous leukemia, and regulating TGF-b1-induced epithelial-mesenchymal transition. However, based on the pathogenetic relationship between miR-30a and cancer in tumorigenesis, we believe that miR-30a may serve as tumor promising biomarker. Moreover, it would offer a therapeutic target for the treatment of cancer.